Measurement of shrinkage during photopolymerization of methacrylate resins by interferometric techniques: Local and global analyses - Arenas, Gustavo Francisco (2016)
Light based measurement techniques have largely proven its efficiency on polymer materials. In this study we describe a method based on specific optical techniques for characterization of dental composites. First, a Dynamic Speckle Pattern (DSP) global analysis was made, which allowed qualitative descriptions of the behavior of samples during polymerization from their upper surface view. This analysis is complemented with local measurements of shrinkage by means of a fiber optic Fizeau Interferometer. Second, a Time History Speckle Pattern (THSP) analysis of different samples was carried out in order to gain a better understanding of the shrinkage development as the polymerization reaction takes place. To show the virtues of these techniques, we applied them to both a commercial resin dental composite and a model resin based on methacrylate monomers. Both techniques could serve as a good comparing test protocol among different commercial resins.